Methotrexate effect on immunogenicity and long-term maintenance of adalimumab in axial spondyloarthritis: a multicentric randomised trial. Issue 1 (9th January 2020) - Ducourau, Emilie; Rispens, Theo; Samain, Marine; Dernis, Emmanuelle; Le Guilchard, Fabienne; Andras, Lucia; Perdriger, Aleth; Lespessailles, Eric; Martin, Antoine; Cormier, Grégoire; Armingeat, Thomas; Devauchelle-Pensec, Valérie; et al.
Abstract : Objectives: Anti-drug antibodies (ADA) are responsible for decreased adalimumab efficacy in axial spondyloarthritis (SpA). We aimed to evaluate the ability of methotrexate (MTX) to decrease adalimumab immunisation. Methods: A total of 110 patients eligible to receive adalimumab 40 mg subcutaneously (s.c.) every other week were randomised (1:1 ratio) to receive, 2 weeks before adalimumab (W-2) and weekly, MTX 10 mg s.c. (MTX+) or not (MTX−). ADA detection and adalimumab serum concentration were assessed at weeks 4 (W4), 8 (W8), 12 (W12) and 26 (W26) after starting adalimumab (W0). The primary outcome was the proportion of patients with ADA at W26. Four years after the study completion, we retrospectively analysed adalimumab maintenance in relation with MTX co-treatment duration. Results: We analysed data for 107 patients (MTX+; n=52; MTX-; n=55). ADA were detected at W26 in 39/107 (36.4%) patients: 13/52 (25%) in the MTX+ group and 26/55 (47.3%) in the MTX− group (p=0.03). Adalimumab concentration was significantly higher in the MTX+ than MTX− group at W4, W8, W12 and W26. The two groups did not differ in adverse events or efficacy. In the follow-up study, MTX co-treatment >W26 versus no MTX or ≤W26 was significantly associated with adalimumab long-term maintenance (p=0.04). Conclusion: MTX reduces the immunogenicity and ameliorate the pharmacokinetics of adalimumab in axial SpA. A prolonged co-treatment of MTX>W26 seems to increase adalimumab long-term maintenance.